COOPERATIVA DE TRABALHO COMO OPÇÃO DE INCLUSÃO SOCIAL: O CASO AMIGOS DO LIXO - Deccache, José Augusto Paes (2012)
The movement of popular cooperatives has grown exponentially in late years. As an alternative organization form to the unemployment crisis, cooperatives assist not only popular basis layers, but also to an expressive contingent of qualified workers with a good living standard. The case study was carried out in a popular cooperative "Friends of the Garbage ", located in Guaratinguetá city - SP. The methodology used will be the unique case study, like data collection techniques and direct observation, analysis of documents of the cooperative and interviews with cooperated people and manager. The general objective was to analyze if the Cooperative of Work mentioned acts as work generating and income. The main concepts of Solidary Economy and work cooperative were defined. The subject was analyzed through the investigation of the perceptions of cooperated people s life conditions before and after the entrance in the respective cooperatives.